2021
DOI: 10.1002/ange.202014208
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrinic Zirconium Metal–Organic Frameworks (MOFs) as Heterogeneous Photocatalysts for PET‐RAFT Polymerization and Stereolithography

Abstract: In this study,p orphyrinic zirconium (Zr) MOFs were investigated as heterogeneous photocatalysts for photoinduced electron transfer-reversible addition-fragmentation chain transfer (PET-RAFT) polymerization of various monomers under abroad range of wavelengths,producing polymers with high monomer conversions,n arrowm olecular weight distributions,l ow dispersity and good chain-end fidelity. Screening of various porphyrinic Zr-MOFs (Zn) containing Zn-metalled porphyrinic ligands demonstrated that MOF-525 (Zn) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…The recyclability is also comparable to previously reported efficient PC, MOF-525 (Zn) (Table S3 † ). 30 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recyclability is also comparable to previously reported efficient PC, MOF-525 (Zn) (Table S3 † ). 30 …”
Section: Resultsmentioning
confidence: 99%
“… 23 The use of PCs for polymerizations offers access to well-defined polymeric materials with complex architectures under mild reaction conditions, 20 and heterogeneous PCs offer added advantages such as easy separation, recycling, and excellent purity of the final product free of catalysts contaminants. 24 Examples include small molecular PCs immobilized on heterogeneous supports, 25 as well as inorganic semiconductors such as perovskites, 26 CdSe quantum dots, 27,28 Bi 2 O 3 , 29 metal–organic frameworks (MOFs), 30–32 and plasmonic Ag 3 PO 4 . 33 Especially, MOFs and their nanosheets have been utilized in photoinduced 3D printing, exhibiting excellent oxygen tolerance and the ability to print complex objects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nazim et al investigated the role of a photopolymerized polymeric thin film in constructing a copper indium gallium selenide solar cell with high efficiency [67]. The group utilized nitrogen-doped graphene quantum dots with transparency, highly emission, and UV-curable properties to fabricate highly dispersed Norland Optical Adhesive (NOA) nanocomposite-based polymeric thin films referred to as poly-QD films [67][68][69][70][71][72][73][74][75][76][77][78][79]. These flexible films served as luminescent downconversion (LDC) layers, which enhanced the function of copper indium gallium selenide solar cells.…”
Section: Applications Of Photopolymers Based On Qpismentioning
confidence: 99%
“…Although conventional light-based 3D printing relies on high energy ultraviolet (UV) light to achieve rapid polymerization rates and correspondingly short build times (~seconds/layer), visible light is emerging as an attractive alternative. [11][12][13] Relative to UV light, visible light is naturally abundant, less expensive, and benign (generally reduced absorption and scattering), which gives it the potential to advance 3D printing of polymeric materials by enabling economical preparation of, for example, cell-laden hydrogels, [14] opaque composites, [15] or multimaterial structures (via wavelength selective reactions). [7,[16][17][18][19] Recently, we demonstrated that a three component photosystem comprising a visible light absorbing photoredox catalyst (PRC) with donor (diphenyliodonium) and acceptor (triphenyl (n-butyl) borate) co-initiators could facilitate photocuring of acrylate-based resins on timescales (~seconds) that were competitive with commercial UV light systems (Figure 1).…”
Section: Introductionmentioning
confidence: 99%